Reducing energy barrier of δ-to-α phase transition for printed formamidinium lead iodide photovoltaic devices. (January 2022) - Xu, Zhenhua; Zeng, Linxiang; Hu, Jinlong; Wang, Zhen; Zhang, Putao; Brabec, Christoph J.; Forberich, Karen; Mai, Yaohua; Guo, Fei
Abstract: Recent progress in perovskite photovoltaics has witnessed a growing interest in formamidinium lead iodide (FAPbI3 ), primarily due to its high efficiency potential and excellent stability. However, the high energy barrier of δ-to-α phase transition presents a major hurdle to fabricate phase-pure α-FAPbI3 layers. Here, we report a two-step phase transition process to deposit high-quality photovoltaic α-FAPbI3 films by printing method. This is realized by judicious selection of a Lewis base N-methyl-2-pyrrolidone (NMP) and its counter Lewis acid, which enables the regulation of intermediary phase to reduce the energy barrier. With fine tuning the phase transition pathway, phase-pure and stable α-FAPbI3 perovskite films are obtained, which yield solar devices with a champion efficiency of 21.35%. The printed mini-modules with active areas of 12.32 cm 2 and 55.44 cm 2 are also fabricated, giving efficiencies of 17.07% and 14.17%, respectively. This work provides new insights of α-FAPbI3 crystallization for constructing efficient and stable printed photovoltaic devices. Graphical abstract: ga1 A two-step crystallization process is realized by intermediary phase tuning to reduce the energy barrier for the printed α-FAPbI3 perovskite. The functional additive is incorporated into the crystal lattice to producing the FA + and I – vacancies, promoting the transformation of δ-to-α Phase FAPbI3 . Highlights: The functional couple NMP-NMPH+ is incorporated into the intermediary phase with FA + and I – vacancies to reduce the energy barrier. Two-step crystallization process is realized for phase-pure α-FAPbI3 formation. Printed α-FAPbI3 for efficient mini-modules.